Hadis Bau Mulut Orang Berpuasa Ditinjau dari Pendekatan Bahasa: Analisis Matan secara Hakiki dan Majazi (The Smell of the Mouth of a Fasting Person from a Linguistic Approach: A Literal and Figurative Analysis of the Text) - Sarah Mitha Amelia; Vera Seftia; Muhammad Sofyan Harahap; Laila Sari Masyhur (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
The hadith regarding the breath of a fasting person, which states that